Exploring the Use of Smartphone Geofencing to Study Characteristics of Alcohol Drinking Locations in High‐Risk Gay and Bisexual Men. (19th March 2019) - Wray, Tyler B.; Pérez, Ashley E.; Celio, Mark A.; Carr, Daniel J.; Adia, Alexander C.; Monti, Peter M.
Abstract : Background: Geofencing offers new opportunities to study how specific environments affect alcohol use and related behavior. In this study, we examined the feasibility of using geofencing to examine social/environmental factors related to alcohol use and sexual perceptions in a sample of gay and bisexual men (GBM) who engage in heavy drinking and high‐risk sex. Methods: HIV‐negative GBM ( N  =   76) completed ecological momentary assessments for 30 days via a smartphone application and were prompted to complete surveys when inside general geofences set around popular bars and clubs. A subset ( N  =   45) were also asked to complete surveys when inside personal geofences, which participants set themselves by identifying locations where they typically drank heavily. Results: Approximately 49% of participants received a survey prompted by a general geofence. Among those who identified at least 1 personal drinking location, 62.2% received a personal geofence‐prompted survey. Of the 175 total location‐based surveys, 40.2% occurred when participants were not at the location that was intended to be captured. Participants reported being most able to openly express themselves at gay bars/clubs and private residences, but these locations were also more "sexualized" than general bars/clubs. Participants did not drink more heavily at gay bars/clubs, but did when in locations with more intoxicated patrons or guests. Conclusions: Geofencing has the potential to improve the validity of studies exploring environmental influences on drinking. However, the high number of "false‐positive" prompts we observed suggests that geofences should be used carefully until improvements in precision are more widely available. Abstract : Geofencing involves creating virtual boundaries around GPS coordinates in order to detect whether users' smartphones are within a specific area of interest. This study showed that geofencing can be used to deliver surveys or interventions via smartphone when recipients are in specific public or personally‐defined drinking locations. With careful planning, this approach could be used to study environmental influences on drinking in near real‐time or provide just‐in‐time interventions when users are in high‐risk locations.